Benjamin Ferencz, Nuremberg prosecutor and peace advocate - Hofmann, Tom (McFarland & Company, 2014)
" At the conclusion of World War II, war crimes tribunals were carried out at Nuremberg, Germany. Justice was meted out for countless war criminals, and Benjamin Ferencz was one of the chief prosecutors for one of the largest murder trials in history. This is the biography of the last living Nuremberg prosecutor. "..